A new penguin cranium from Antarctica and its implications for body size diversity during the Eocene - Haidr, Nadia Soledad; Acosta Hospitaleche, Carolina Ileana Alicia (Neues Jahrbuch für Geologie und Paläontologie - Abhandlungen)
Although penguins have a very abundant fossil record in Antarctica, very few cranial elements have been found so far, and in all the cases the specimens are incomplete. We describe a new cranium of a medium-sized penguin from the late Eocene Submeseta Formation in Marambio/ Seymour Island, Antarctica. Its morphology allows us to establish a common cranial pattern for all known Eocene taxa (including South American, Antarctic and probably Oceanian species), with very different proportions between cranium and post-cranium from those of modern penguins. These Paleogene fossils exhibit a small neurocrania, extremely elongated bills, large occipital condyles, and strong cranio-mandibular articulations. Fil: Haidr, Nadia Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto de Biología de Organismos Marinos; Argentina Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina